Pelatihan Penyelenggaraan Shalat Jenazah untuk Meningkatkan Pengetahuan pada Generasi Z di Kota Blitar - Nik Haryanti; Endah Siswati; Camara Miko Surbakti (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service research aims to improve the knowledge and skills of Generation Z in Blitar City in organizing funeral prayers according to Islamic law. This activity is motivated by the low understanding of the younger generation regarding the procedures for performing funeral prayers, even though it is part of the fardhu kifayah obligation that should be understood by every Muslim. Through this training activity, it is hoped that Generation Z will have theoretical and practical skills in performing funeral prayers correctly and raise awareness of the importance of social and spiritual responsibility in community life. The method used is Participatory Action Research (PAR) by actively involving participants in two stages of activities, namely providing material on the laws, pillars, and prayers of funeral prayers, as well as direct practice of its implementation guided by competent speakers. The results of the study showed that this training went well and received a positive response from the participants. Based on the results of the pre-test and post-test, there was an average increase in knowledge scores of 42%, which indicates a significant increase in the understanding and skills of participants. Participants were able to explain the pillars, valid conditions, and procedures for funeral prayers correctly. In addition to increasing knowledge, this activity also strengthens religious values, social responsibility, and spiritual awareness among the younger generation. Therefore, this training is effective in shaping a Generation Z that is knowledgeable, moral, and committed to the teachings of Islam in its entirety.